Please I need you to show work
The first thing you need to do is recognize that X is the same thing as 1X. So we can rewrite the equation like this:
1X-5X+52=23 Now subtract 5X from 1X which would give us -4X
-4X +52=23 Now let's move the 52 by subtracting 52 from each side of the equation. We can manipulate any equation as long as we do so on both sides of the equation. Like this:
-4X+52-52=23-52 All we have to do know is solve the portions of the equation that we know.
52-52=0 and 23-52=-29 so we would end up with:
-4X=-29 Now we divide each side by -4
-4X/-4=-29/-4 Which would give us:
I hope this made sense, if there is any part of this you don't understand, let me know and I will explaing it further.